iMirabilis2: Cabo Verde oceanographic insights - Mosquera-Giménez, Ángela; Vélez-Belchí, Pedro; Mouzo-Bellino, Iván; Huvenne, V.A.I.; Orejas, Covadonga (2021)
Cabo Verde Islands are located between the North Equatorial Current (NEC) and the North Equatorial Counter Current (NECC). When the NECC reaches Africa, it splits in two currents, an eastward and a northward flow. This later flow joints the NEC forming a front known as the Cabo Verde Frontal Zone, that acts as a barrier between the North Atlantic Central Waters (NACW) and the South Atlantic Central Waters (SACW). In addition, this northward flow produces a cyclonic circulation in the region of Cabo Verde, called the Guinea Dome, and therefore an upwelling in this area. During the iMirabilis2 expedition, 22 CTD cast were performed in order to characterize the hydrographic conditions and to determine the water mass distribution in the main study areas, to find out its effects on the distribution of benthic organisms. Especial attention was put on the characterization of the Cadamosto seamount. Seamounts are underwater mountains which create a perturbation in the oceanic flow. This perturbation under idealized circumstances, known as Taylor columns, has the potential to isolate the oceanic circulation over the summit from the ocean circulation in the open waters. This can lead to the occurrence of upwelling phenomena that enrich the ecosystem. In this work, we show an overview of the preliminary results of the oceanographic studies conducted during the iMirabilis2 expedition.